Oncology of CNS Tumors - Tonn, Jörg-Christian; Westphal, Manfred; Rutka, J. T. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
The rapidity with which new diagnostic procedures and treatment modalities are being developed within neuro-oncology means that experts continually have to strive to ensure that their knowledge remains up-to-date. With this in mind, the editors have prepared a new, revised edition of Neuro-oncology of CNS Tumors that takes account of the very significant advances made since publication of the well-received first edition. The clear structure of the first edition has been retained as it ensures that the book will serve as an easy-to-use reference, providing ready guidance on diagnosis and treatment. Each chapter addresses a particular disease, and great efforts have been made to include all findings and other information likely to be relevant in clinical practice. Once again, the contributors have been carefully selected and are leading experts on their subject. This book will prove of great value to both practicing clinicians and researchers in the field of translational neuro-oncology.